Circulating anti‐Müllerian hormone and breast cancer risk: A study in ten prospective cohorts. Issue 11 (8th February 2018) - Ge, Wenzhen; Clendenen, Tess V.; Afanasyeva, Yelena; Koenig, Karen L.; Agnoli, Claudia; Brinton, Louise A.; Dorgan, Joanne F.; Eliassen, A. Heather; Falk, Roni T.; Hallmans, Göran; Hankinson, Susan E.; Hoffman‐Bolton, Judith; et al.
Abstract : A strong positive association has been observed between circulating anti‐Müllerian hormone (AMH), a biomarker of ovarian reserve, and breast cancer risk in three prospective studies. Confirming this association is important because of the paucity of biomarkers of breast cancer risk in premenopausal women. We conducted a consortium study including ten prospective cohorts that had collected blood from premenopausal women. A nested case–control design was implemented within each cohort. A total of 2, 835 invasive (80%) and in situ (20%) breast cancer cases were individually matched to controls ( n = 3, 122) on age at blood donation. AMH was measured using a high sensitivity enzyme‐linked immunoabsorbent assay. Conditional logistic regression was applied to the aggregated dataset. There was a statistically significant trend of increasing breast cancer risk with increasing AMH concentration ( p trend across quartiles <0.0001) after adjusting for breast cancer risk factors. The odds ratio (OR) for breast cancer in the top vs . bottom quartile of AMH was 1.60 (95% CI = 1.31–1.94). Though the test for interaction was not statistically significant ( p interaction = 0.15), the trend was statistically significant only for tumors positive for both estrogen receptor (ER) and progesterone receptor (PR): ER+/PR+: ORQ4–Q1 = 1.96, 95% CI = 1.46–2.64, p trend <0.0001; ER+/PR−: ORQ4–Q1 = 0.82, 95% CI = 0.40–1.68, p trend = 0.51; ER−/PR+: ORQ4–Q1 = 3.23, 95% CI = 0.48–21.9, p trend = 0.26; ER−/PR−: ORQ4–Q1 = 1.15, 95% CI = 0.63–2.09, p trend = 0.60. The association was observed for both pre‐ (ORQ4–Q1 = 1.35, 95% CI = 1.05–1.73) and post‐menopausal (ORQ4–Q1 = 1.61, 95% CI = 1.03–2.53) breast cancer ( p interaction = 0.34). In this large consortium study, we confirmed that AMH is associated with breast cancer risk, with a 60% increase in risk for women in the top vs . bottom quartile of AMH. Abstract : What's new? To make informed decisions about screening and prevention, women need tools to accurately assess their breast cancer risk. Young women have few predictive biomarkers to look to; estrogen and progesterone are only weakly predictive before menopause. Anti‐Muellerian hormone (AMH), which strongly correlates with age at menopause, may also correlate with breast cancer risk, according to some previous data. Here, the authors test this correlation by conducting nested case‐control studies within ten different cohorts. They found that breast cancer risk increased along with increasing AMH concentration, confirming this hormone as a possible biomarker for breast cancer.